"It's complicated and nuanced": Teaching genre awareness in English for general academic purposes. Issue 57 (May 2022) - Tardy, Christine M.; Buck, Rachel Hall; Jacobson, Brad; LaMance, Rachel; Pawlowski, Madelyn; Slinkard, Jennifer R.; Vogel, Stefan M.
Abstract: This article shares a year-long qualitative study of six writing instructors' experiences with genre-based pedagogy (GBP). Through a collaborative research approach, the study examines these teachers' perspectives on their challenges and successes with GBP in an English for general academic purposes writing classroom. Findings highlight challenges related to course aims, content, and structure, as well as successes related to the ability to use their content knowledge of genre to troubleshoot and further develop their use of GBP in the classroom. The findings suggest that teacher pedagogical content knowledge of genre develops in interaction with teachers' practice and should be supported by robust and on-going teacher training and support. The paper concludes by offering examples of how teacher support might address the challenges unique to genre-based pedagogy. Highlights: We traced six teachers' experiences with genre pedagogy in a general EAP context. Genre-based pedagogy raised particular challenges in the general EAP context. Formal education and classroom teaching both developed teachers' pedagogical content knowledge of genre. Reflecting on their teaching helped teachers adapt genre theories to practice.